PENGARUH PERSEPSI KUALITAS PRODUK DAN DIFFERENSIASI PRODUK TERHADAP PERILAKU PERPINDAHAN MERK SEPEDA MOTOR YAMAHA DI KABUPATEN PURWAKARTA - Indra Maulana (Eqien - Jurnal Ekonomi dan Bisnis, 2017)
Business competition makes consumers benefit from the many brands that sell the same product with different variations. therefore the bargaining power of consumers against producers become more powerful, because the consumer has a variety of alternative product variations that can meet their needs. Various alternative options of this product can lead consumers to switch brands from one brand to another brand. The purpose of this study was to determine how much influence the perception of product quality and product differentiation on the displacement behavior Yamaha brand motorcycles in the town of Purwakarta. This research includes research into descriptive. The collection of primary data through questionnaires by sampling using Probability Sampling technique. Data analysis technique used in this research is the validity of the data, the reliability of the data, the normality of the data, mutikolieritas, heterokedastisitas. While the test design using multiple linear regression data analysis, the correlation coefficient, the coefficient of determination while to test the truth of the hypothesis performed with partial and Test Simultaneous Test. The results showed that the perception of product quality and product differentiation has a strong relationship to the displacement behavior Yamaha brand motorcycles in Purwakarta. This is evidenced from the results obtained in testing the hypothesis that t value perception of the quality of the product = 4,640> t table ¬ = 1,984. While the value of product differentiatin t = 4,226> 1,984. With the level of significance of both is (0.000 and 0.000) less than 0.05. while simultaneously test results obtained arithmetic sum of 95 735 F and F table at 3:09 with a significance level greater than 0:00 <0.05. The value of the correlation coefficient of 0776 as well as the coefficient of determination = 60.2% subsequent multiple regression equation obtained was Y = 20,329 + -0150 -0303 X1 + X2 + e. It means that any increase in the perception of the product quality 1% then the displacement behavior of the brand will decrease by 0.150. And if the product differentiation increased by 1%, the displacement behavior of the brand will be down 0.303. Keywords: Perception of Product Quality, Product Differentiation, Brand Switching Behavior